DAMPAK UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK (UU ITE) TERHADAP PERUBAHAN HUKUM DAN SOSIAL DALAM MASYARAKAT - Sidik, Suyanto (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
The spectacular development of the information technology in communication. has greatly impact the development of law and social interaction. Beside giving a positive contribution for the information technology media used, howewer, it also has caused negative impact in another part. In order to prevent this, the Indonesian government has initiated a new regulation as the Information and Electronic Transaction Law No. 11 year 2008. The regulation is the prior Indonesian law, which arranged the implementation of information technology communication. The objectived of this research is to discuss the impact of the information and electronic transaction and its implementation in Indonesian. The method used library research, which connected with the implementation in the real field, and analyzed descriptively. It can be concluded that: (1) The regulation number 11 year 2008 give the protection to the of the information and electronik transaction society. (2) it shoud be socialized to the community in order to achive the law security for the information technology user and promotor.